2015
DOI: 10.1080/08841241.2015.1042098
|View full text |Cite
|
Sign up to set email alerts
|

International student satisfaction with, and behavioural intentions towards, universities in Victoria

Abstract: International students make a vital contribution to the Australian economy. Due to their importance, a number of studies have been undertaken to examine the living experiences, attitudes and behaviours of international students in Australia. However, very few studies have examined international students' overall satisfaction with their university experience. The primary objective of this paper is to measure the influence of six individual university service factors on international students' satisfaction, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…The first determinant of international student loyalty is generally considered to be disconfirmation [21,22]. This construct originates from the expectation-disconfirmation theory that is widely used in the consumer behavior literature [23][24][25].…”
Section: Disconfirmationmentioning
confidence: 99%
See 2 more Smart Citations
“…The first determinant of international student loyalty is generally considered to be disconfirmation [21,22]. This construct originates from the expectation-disconfirmation theory that is widely used in the consumer behavior literature [23][24][25].…”
Section: Disconfirmationmentioning
confidence: 99%
“…In the case of international students, their disconfirmation could be related to expectations and performances of tangible components of higher education services, namely lecture halls, student service centers, libraries, laboratories, computer rooms, etc., and intangible components of higher education services such as the availability of lecturers and tutors, their expertise, their teaching methods, their attitudes to students, etc. [21]. As explained by Lankton and McKnight [27] (p. 89), disconfirmation is "a subjective post-usage comparison that can result in one thinking performance was better, the same as, or worse than expected."…”
Section: Disconfirmationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies have shown their quality and delivery is questionable and thus, may not be providing international students with a supportive campus environment (Khawaja & Dempsey, 2008;Miliszewska & Sztendur, 2012). As they are not sharing in the supports that are offered to domestic students, it is understandable that international students are expressing a lack of contentment resulting in their social disconnectedness and homesickness (Alzamel, 2014;Hendrickson, Rosen, & Aune, 2011;Mark, Bodycott & Ramburuth, 2015;Padlee & Reimers, 2015). As a result of international students' lower levels of social support, higher mismatched expectations and greater use of dysfunctional coping strategies, they are placed in more vulnerable situations than the domestic students (Khawaja & Dempsey, 2008).…”
Section: Inadequate Supportsmentioning
confidence: 99%
“…Roberts and Dunworth (2012) suggest that insufficient support services may prevent international students from fully functioning at university. Likewise, Padlee and Reimers (2015) showed that academic services have a direct impact on international student satisfaction. Finally, some of the contradictory research results indicate a lack of precision inherent in early stages of researching a domain; care should be taken before labeling certain culture-specific learning styles as deficient.…”
Section: Limitations and Future Researchmentioning
confidence: 99%